Palacký’s History and the Historical Memory of the Nation - Činátl, Kamil (Dějiny – teorie – kritika, 2009)
This article analyzes the role that František Palacký’s multi-volume History of the Czech Nation in Bohemia and Moravia had in constituting the modern historical memory of the Czech nation. It starts from the concept of collective memory as defined by the sociologist Maurice Halbwachs, and focuses chiefly on the description and interpretation of collectively shared images of the past. The article examines the relationship between historiography and historical painting in the late nineteenth and early twentieth centuries, mainly in the works of Mikoláš Aleš, Luděk Marold, and Václav Brožík. Using specific examples, such as battle fields and symbolic architecture, the article considers the ability of the landscape and places on it to become media of historical memory.